Hey there!
Here's the answer.
9(y-4)=6y-45 --> Write the problem.
9y-36=6y-45 --> Distribute 9 into y-4.
3y-36=-45 --> Subtract 6y on both sides of the equation.
3y=-9 --> Add 36 to both sides of the equation.
y=-3 Divide 3 on both sides of the equation.
So the answer is y=-3.
Hope it helps!
2007-10-08 10:47:14
·
answer #1
·
answered by ? 6
·
0⤊
0⤋
Ok
9( y - 4 ) = 6y - 45
use the distributed property
9y-36=6y-45
you then need to subtract 36 from both sides
9y=6y-9
subtract 6y from both sides
3y=-9
divide each side by 3
y=-3
there you go!!!! the answer is -3
Good luck in Math!!!! =)
2007-10-09 17:40:15
·
answer #2
·
answered by ... 4
·
0⤊
0⤋
Expand out the equation, then collect like terms on one side;
9(y - 4) = 6y - 45
9y - 36 = 6y - 45
9y - 6y = 36 - 45
3y = -9
y = -9/3
y = -3
You can check the answer by subsitiuting the answer back into the equation, both side should be equal.
2007-10-08 17:44:41
·
answer #3
·
answered by skibz26 4
·
0⤊
0⤋
9(y-4) = 6y - 45
Use the distributive property (multiply 9 by y and 9 times 4)
9y - 36 = 6y - 45
Add 36 to both sides
9y = 6y - 9
Subtract 6y from both sides
3y = -9
Divide both sides by 3
y=-3
2007-10-08 17:43:57
·
answer #4
·
answered by Lindsay 3
·
1⤊
0⤋
9(y - 4) = 6y - 45
distribute the 9 to get:
9y-36 = 6y-45
subtract 6y from both sides to get:
3y-36 = -45
add 36 to both sides to get:
3y = -9
divide both sides by 3 to get:
y = -3
plug answer in equation to check
9 ((-3) - 4) = -63
6(-3) - 45 = -63
2007-10-08 17:41:51
·
answer #5
·
answered by Mrs. Bear 4
·
0⤊
0⤋
i assume u are trying to find the value of y
first multiply 9 into the brackets
9y-36=6y-45
bring all common elements on the same sides (all ys on one side all non variables on other)
9y-6y=-45+36
add/subtract
3y=-9
divide 3 off both sides
y=-3
thus y=-3
2007-10-08 17:42:34
·
answer #6
·
answered by DUDE 2
·
1⤊
0⤋
9( y - 4 ) = 6y - 45
9y - 36 = 6y -45
9y-6y = 36-45
3y = -9
y =-3
2007-10-08 17:42:04
·
answer #7
·
answered by Any day 6
·
0⤊
0⤋
9 ( y - 4 ) = 9y - 36
9y - 36 = 6y - 45
therefore:
9y - 6 y = - 45 + 36
3y = -9
y = -9 / 3
y = -3
2007-10-08 17:45:14
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
9(y-4)=6y-45
Distribute the 9
9y-36=6y-45
subtract 6y from both sides
3y-36=-45
add 36 to both sides
3y=-9
Divide both sides by 3
y=-3
2007-10-08 17:42:11
·
answer #9
·
answered by soccerlover4eternity 1
·
0⤊
0⤋
open the parentheses: 9y-36=6y-45
put variables on one side: 9y-6y=36-45
when crossing over equals sign, change polarity (+ to -, - to +)
3y=-9
y=-3
2007-10-08 17:51:05
·
answer #10
·
answered by lazymonkey915 2
·
0⤊
0⤋